FINANCIAL SECURITY OF PLAYERS IN THE FINANCIAL MARKETS IN THE CONDITIONS OF GLOBALIZATION AND STRATEGIC DEVELOPMENT - Valeriia Prokopenko, Nadiya Doroshenk?, Maryna Ponomarova, Natalia Kornieva, Dmitriy Babych (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The transfer of capital takes place through the sale of financial assets that reflect the right to receive income on invested capital, the financial market can be defined as a market in which financial assets are issued, sold, and bought. We have determined the financial security of players in the financial markets in the context of globalization and strategic development. The composition of the financial market is defined, which includes the money market, the capital market, and the foreign exchange market. The National Bank of Ukraine works in the financial market to achieve monetary policy goals. Rational use of fixed assets and functional capacities of the budgetary institution is substantiated, which primarily contributes to the improvement of all technical and economic indicators, and in particular to increase the volume of activity, reduce the complexity of the unit of work performed or services provided. The main reasons for the growth of the balance deficit, which have an impact on the deterioration of foreign trade conditions and the system of distribution of national income between the consumer and productive sectors of the economy are singled out, the Central Bank significantly affects the equilibrium point. The interbank or non-cash market means all purchase and sale transactions that take place between banks and ensure the execution of customer orders and conversion transactions by the financial institutions themselves. In turn, the National Bank of Ukraine, as the main financial institution, undoubtedly has a regulatory function in the foreign exchange market. An assessment of the state of the non-cash and cash foreign exchange market is given. The share of operating structural subdivisions of banks (except for insolvent banks) in Ukraine has been determined. The main strategic indicators of the financial market that will affect the effective regulation of the financial sector and the integration of the financial market of Ukraine into the global financial space are revealed.